>35% 5-junction space solar cells based on the direct bonding technique. (December 2021) - Li, Xinyi; Li, Ge; Lu, Hongbo; Zhang, Wei
Abstract: Multijunction solar cells are the highest efficiency photovoltaic devices yet demonstrated for both space and terrestrial applications. In recent years five-junction cells based on the direct semiconductor bonding technique (SBT), demonstrates space efficiencies >35% and presents application potentials. In this paper, the major challenges for fabricating SBT 5J cells and their appropriate strategies involving structure tunning, band engineering and material tailoring are stated, and 4-cm 2 35.4% (AM0, one sun) 5J SBT cells are presented. Further efforts on detailed optical managements are required to improve the current generating and matching in subcells, to achieve efficiencies 36%–37%, or above.